Study, Evaluation, and Monitoring of Bridge Bearing in Accelerated Bridge Construction (ABC) - Gautam, Bishnu Gupt; Kim, Chang Kyu (KTFT Journal, 2024)
The study starts by going over the several kinds of bridge bearings that are frequently used, such as friction pendulum, pot, and elastomeric bearings. It examines particular difficulties and demands these bearings have in ABC practice including their quick installation, off-site construction, and compatibility with prefabricated bridge components. By addressing the unique challenges and requirements of bridge bearings, including their evaluation and long-term monitoring, this research and contributes to the advancement of accelerated construction techniques, ultimately leading to safer, more efficient, and cos infrastructure solutions.